Comparison of aerosol lidar retrieval methods for boundary layer height detection using ceilometer aerosol backscatter data - Caicedo, V; Rappenglück, B; Lefer, B; Morris, G; Toledo, D; Delgado, R (Copernicus Publications, 2017)
Three algorithms for estimating the boundary layer heights are assessed: an aerosol gradient method, a cluster analysis method, and a Haar wavelet method. Over 40 daytime clear-sky radiosonde profiles are used to compare aerosol backscatter boundary layer heights retrieved by a Vaisala CL31 ceilometer. Overall good agreement between radiosonde- and aerosol-derived boundary layer heights was found for all methods. The cluster method was found to be particularly sensitive to noise in ceilometer signals and lofted aerosol layers (48.8% of comparisons), while the gradient method showed limitations in low-aerosol-backscatter conditions. The Haar wavelet method was demonstrated to be the most robust, only showing limitations in 22.5% of all observations. Occasional differences between thermodynamically and aerosol-derived boundary layer heights were observed.